Gonadotrophin-releasing hormone agonist treatment for sexual offenders: A systematic review. (October 2017) - Lewis, Alexandra; Grubin, Don; Ross, Callum C; Das, Mrigendra
Background: Sexual offending is a significant international issue causing long-term consequences for victims, perpetrators and society. Aims: The purpose of this study was to review the existing research data assessing the efficacy of gonadotrophin-releasing hormone agonists for treating adult, male, sexual offenders. Method: The method of this review involved the examination of studies involving participants prescribed at least one month of a gonadotrophin-releasing hormone agonist for the purposes of reducing sexual drive related to offending. The primary outcome measures were recidivism rates and sexual functioning. Secondary outcome measures included assessment of side effects and effects on interpersonal/psychiatric functioning. Studies in the English language that were dated 1969–2015 were included. Results: Twelve eligible studies (323 participants) were identified. A reduction in a variety of measures of sexual functioning and/or risk was found in all studies. Robust recidivism data was limited. Medication was rarely described as ineffectual. All studies reported side effects. Reduction in bone density and potential long-term reduction in fertility in some subjects were issues of concern. Conclusion: Whilst identified studies showed promising results with respect to sexual functioning, challenges in performing randomised control trials in this subject group meant that included studies were methodologically limited. This review recommends that future research must be performed before the effectiveness and tolerability of gonadotrophin-releasing hormone agonists in this population can be confirmed.